Environmental Assessment of Polycyclic Aromatic Hydrocarbons pollutants in the waters of the side branches of the Shatt Al-Arab River - Al-Saad, Hamid T.; Al-Khion, Dhfar. Dh.; Majeed, Ebtihal S.; Hantoush, Abas A.; Saleh, Salah M.; Alhello , Abdulzahra A. (Iraqi Journal of Aquaculture, 2021)
This study was conducted in the water branches of Shatt Al-Arab River. Water samples were collected from six stations during 2013. Gas chromatography was used to identify the concentrations and type of Polycyclic Aromatic Hydrocarbons (PAHs). Total concentration of polycyclic aromatic hydrocarbons (PAHs) in water ranged from 7.24 to 17.39 ng/l. The sources of PAHs in waters were Pyrogenic and Petrogenic with predominance of etehahthNaN, Fluoreneand B(b+ k) fluoranthene the most presence and focused from PAHs compound which indicate a Pyrogenic, as well as presents of Indeno (1,2,3,cd) pyrene+ dibenzo, Benzo(g, h, i) perylene in high concentration which indicate a Petrogenic origin . This study is a first of its kind in the branches of Shatt Al-Arab River and its represent as a background for futures studies.